RESEARCH OF THE DYNAMICS OF A DOUBLY FED MACHINE WITH A RELAY CONTROL SYSTEM ORIENTED BY THE STATOR VOLTAGE VECTOR - KLIUIEV, OLEH (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Vector control systems for AC machines have two or more control channels. The coordinate of the electric machine  which is determined by the technological process  is regulated by the active power channel. In the reactive power channel  by changing the magnitude of the magnetic flux, it is possible to improve the energy performance of AC drives. Thus  in the vector control systems of doubly fed machines (DFM) the stator flux coupling vector is most often taken as the reference. However  it is also possible to regulate the angular speed of the rotor and the reactive power of the stator at the same time in vector control systems of DFM oriented along the stator voltage vector. Similar to field-oriented systems  the capabilities of such control systems are based on the property of practical perpendicularity of voltage vectors and stator flux coupling in stable modes. This is especially true for high-power electric machines in which the active resistance of the stator practically does not affect the angle between these vectors. When the electrical network  (stator) voltage is stable  the control system can be oriented according to the stator voltage vector in both driving and generator modes of operation of the DFM. In the paper from the equations of the generalized electric machine  the equations of the doubly  fed machine were obtained in the coordinate axes oriented along the stator voltage vector. In the case of stability of the voltage of the electrical network and the absence of commutations of the stator windings in these coordinate axes  it is possible to build a two-channel control system for the reactive power of the stator circuit and the angular speed of the rotor. Such an electric drive is created on the basis of an asynchronous machine with a phase rotor to which a frequency converter with vector control is connected. An analysis of the structure of the DFM model  was carried out in the axes oriented along the stator voltage vector. A relay-vector control system of DFM with a structure of the reactive power regulation circuit of the stator circuit, which differs from known structures has been developed. The dynamics of the DFM with a synthesized control system was researched by the method of mathematical modeling.
Keywords: doubly fed machine; stator voltage reference vector; orthogonal rotating coordinate system; relay controller; mathematical model